The intruder [large type] - McFadden, Freida (Thorndike Press large print dynamic drama., 2025)
As a hurricane rages outside her remote cabin, Casey discovers a blood-covered girl hiding near her kitchen. The girl refuses to speak or drop her knife, and as the storm worsens, Casey uncovers a chilling secret. With danger mounting, Casey must unravel the truth--before the girl silences her for good.